The candidate - Wiehl, Lis W.; Stuart, Sebastian (Wiehl, Lis W. Newsmakers novels., 2016)
"How far would a candidate go to become President of the United States? In covering the presidential election campaign, star newsmaker Erica Sparks notices that favored candidate Senator Mike Ortiz seems dependent on his wife to an unnatural degree. Celeste Ortiz is a brilliant and glamorous billionaire who--along with her best friend and confidant Lily Lau--has engineered her husband's meteoric rise. The White House is within their reach. But the more Erica investigates the Ortizes' strange relationship, the more intrigued she becomes. Erica begins an investigation. But everyone material to her probe ends up dead. With each death, her foreboding grows. Is she next? And can she find out in time if the country's beloved candidate is what he seems, or a threat to national security?"--